A genus-level classification of the family Thraupidae (Class Aves: Order Passeriformes) - Burns, Kevin J.; Unitt, Philip; Mason, Nicholas A. (Zootaxa, 2016)
The tanagers (Thraupidae) are a major component of the Neotropical avifauna, and vary in plumage colors, behaviors, morphologies, and ecologies. Globally, they represent nearly 4% of all avian species and are the largest family of songbirds. However, many currently used tanager genera are not monophyletic, based on analyses of molecular data that have accumulated over the past 25 years. Current genus-level classifications of tanagers have not been revised according to newly documented relationships of tanagers for various reasons: 1) the lack of a comprehensive phylogeny, 2) reluctance to lump existing genera into larger groups, and 3) the lack of available names for newly defined smaller groups. Here, we present two alternative classifications based on a newly published comprehensive phylogeny of tanagers. One of these classifications uses existing generic names, but defines them broadly. The other, which we advocate and follow here, provides new generic names for more narrowly defined groups. Under the latter, we propose eleven new genera (Asemospiza, Islerothraupis, Maschalethraupis, Chrysocorypha, Kleinothraupis, Castanozoster, Ephippiospingus, Chionodacryon, Pseudosaltator, Poecilostreptus, Stilpnia), and resurrect several generic names to form monophyletic taxa. Either of these classifications would allow taxonomic authorities to reconcile classification with current understanding of tanager phylogenetic relationships. Having a more phylogenetically accurate classification for tanagers will facilitate the study and conservation of this important Neotropical radiation of songbirds.